Bimbingan Keagamaan Melalui Pengajian Rutin Untuk Meningkatkan Kesadaran Beragama Masyarakat - Nurfadillah, Az Zahra Fikriyatun; Arifin, Isep Zaenal; Fajar, Dadang Ahmad (Irsyad: Jurnal Bimbingan, Penyuluhan, Konseling, dan Psikoterapi Islam, 2023)
The purpose of this study was to determine the initial condition of the community's religious awareness, the process of implementing religious guidance through regular recitations and the results of religious guidance through regular recitation of the community's religious awareness. The research method uses a sociocultural approach with the paradigm used in this study, namely the constructivism paradigm using descriptive methods. Data collection techniques used are direct observation and interviews. The results of this study indicate that the religious awareness of the community in Cipendawa Village has increased after the community participated in religious guidance activities through regular recitations at the two mosques, namely the Jam'i Al-Huda mosque and the Jam'i Al-Hikmah mosque. This increase can be seen from the fulfillment of the three aspects of religious awareness, namely affective and conative aspects, cognitive aspects and motor aspects.